Unexpected metal-promoted transformation yields an anthrylmethyl spiroanthracene - Kumbhar, Anupa A.; Kumbhar, Avinash S.; Puranik, Vedavati G. (Journal of Organic Chemistry, 2008)
The isolation and characterization of an unusual spiroanthracene, from the reaction of bisdichlororuthenium(II)bi-pyridine dihydrate with 3-(9-anthrylmethyl)pentane-2,4-dione (AMPD), is reported. This metal-promoted formation of spiroanthracene has been obtained for the first time during the synthesis of metal complexes.